Clinical neurology: why this still matters in the 21st century. Issue 2 (29th May 2014) - Nicholl, David J; Appleton, Jason P
Abstract : This review argues that even with the tremendous advances in diagnostic neuroimaging that the clinical skills involved in clinical neurology (ie, history, examination, localisation and differential diagnosis) remain key. Yet a number of recent audits suggest that large numbers of patients are failing to be assessed properly with a risk of patient harm, costly, unnecessary or inappropriate investigations, or delayed diagnosis. We review some of the reasons why patients are not being assessed properly neurologically, in part as many doctors have limited neurological exposure and are hence neurophobic. We propose that a solution to these issues centres around ensuring that a core set of basic neurological skills is taught at an undergraduate level, whereas higher level skills, such as the use of heuristics, are taught at postgraduate level.